PERBANDINGAN EFEKTIFITAS PENGGUNAAN EARMUFF DAN MUROTAL AL- QURAN TERHADAP TANDA VITAL BAYI PREMATUR - Sofiyah, Yusi (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2024)
Premature birth is the second leading cause of death in children under five years after pneumonia. Premature babies must adapt to the extrauterine environment in a situation where the baby's body functions are not optimal. This often causes stress in premature babies. Loud noises in the treatment room, besides causing stress to the neonate can also cause hearing loss and the use of mechanical ventilation to cause noise. The use of earmuff in premature infants treated in the NICU room can significantly increase arterial oxygen saturation, less frequent motor responses, and decrease in pulse and respiratory rate. Murotal can reduce stress, activate natural endorphins, increase feelings of relaxation and divert attention and fear, anxiety and tension. Using the post test design method, and taking respondents with consecutive sampling, this study aims to determine the differences in the effectiveness of the use of earmuff and murrotal Al-Qur'an on the vital signs of the baby. There is an effect of using earmuff on the pulse, respiration and vital signs of the baby. There is a relationship between of murrotal Qur'an to the pulse of premature infants. There is no significant effect between earmuff installation and murrotal administration. Nurses are expected to be able to implement the results of this research.